Phospholipase Dζ Enhances Diacylglycerol Flux into Triacylglycerol . Issue 1 (21st March 2017) - Yang, Wenyu; Wang, Geliang; Li, Jia; Bates, Philip D.; Wang, Xuemin; Allen, Doug K.
Abstract : Phospholipase D increases the production of triacylglycerol in Camelina sativa seeds. Abstract: Plant seeds are the primary source of triacylglycerols (TAG) for food, feed, fuel, and industrial applications. As TAG is produced from diacylglycerol (DAG), successful engineering strategies to enhance TAG levels have focused on the conversion of DAG to TAG. However, the production of TAG can be limited by flux through the enzymatic reactions that supply DAG. In this study, two Arabidopsis phospholipase D ζ genes ( AtPLDζ1 and AtPLDζ2 ) were coexpressed in Camelina sativa to test whether the conversion of phosphatidylcholine to DAG impacts TAG levels in seeds. The resulting transgenic plants produced 2% to 3% more TAG as a component of total seed biomass and had increased 18:3 and 20:1 fatty acid levels relative to wild type. Increased DAG and decreased PC levels were examined through the kinetics of lipid assembly by [ 14 C]acetate and [ 14 C]glycerol incorporation into glycerolipids. [ 14 C]acetate was rapidly incorporated into TAG in both wild-type and overexpression lines, indicating a significant flux of nascent and elongated acyl-CoAs into the sn -3 position of TAG. Stereochemical analysis revealed that newly synthesized fatty acids were preferentially incorporated into the sn -2 position of PC, but the sn -1 position of de novo DAG and indicated similar rates of nascent acyl groups into the Kennedy pathway and acyl editing. [ 14 C]glycerol studies demonstrated PC-derived DAG is the major source of DAG for TAG synthesis in both tissues. The results emphasize that the interconversions of DAG and PC pools can impact oil production and composition.